Management of Orchid Pests with Silwet® L-77 and Horticultural Oils - Robert A. Cating; Marjorie A. Hoy; Aaron J. Palmateer (EDIS)
IFAS researchers evaluated the ability of the surfactant Silwet® L-77 to improve the efficacy of horticultural oils in controlling boisduval scale and mite infestations in orchids. This 3-page fact sheet reports the results and provides homeowners with directions for its use. Written by R. A. Cating, M. A. Hoy, and A. J. Palmateer, and published by the UF Department of Plant Pathology, November 2011.